Non-isolated high voltage gain DC to DC converter based on the diode a capacitor switches - Ibraheem Jawad Billy; Jasim Farhood Hussein (Institute of Advanced Engineering and Science, 2022)
Many researchers have put great endeavor to develop DC converter’s designs, into studying how to increase voltage gain with low switching stress and low ripple current. This paper has proposed a circuit to boost the voltage with a high gain conversion ratio. It is a combined adverse parallel two boost conversion. Two inductors are connected on both sides of the input source to decrease the current-ripple of the input current and output sides utilizing the interleaving technique. The proposed converter integrated with an active-network circuit is based on multiplier cells and two output capacitors. The voltage gain and voltage stresses across power semiconductors have been determined using a steady-state analysis. In addition, the input current- ripple and output voltage-ripple are analysis have been reported. This converter's inductors operate in a continuous conduction mode (CCM). The designed converter is capable of achieving significant voltage gain while maintaining a low duty ratio. Furthermore, the active switches and output diodes are under low voltage stress. As a result, low voltage components can be used to decrease conduction loss and cost. Finally, this converter was simulated in MATLAB/Simulink software to verify the theoretical calculations.